A Novel Compound Heterozygous Mutation in the DNAH11 Gene Found in Neonatal Twins With Primary Ciliary Dyskinesis - Dong, Shumei; Bei, Fei; Yu, Tingting; Sun, Luming; Chen, Xiafang; Yan, Hui (Frontiers in Genetics, 2022)
Background: Primary ciliary dyskinesia (PCD) is a rare genetically heterogeneous disorder of motile cilia. Common features of PCD include upper and lower respiratory tract disease, secretory otitis media, situs inversus and fertility problems. To date, although several PCD-associated genes have been identified, the genetic causes of most PCD cases remain elusive. Methods: In this case study, we analyzed the clinical and genetic data of one case of monochorionic diamniotic twins which were suspected of having PCD on the basis of clinical and radiological features including situs inversus, recurrent wet cough and sinusitis as well as varying degrees of respiratory distress. Whole-exome sequencing was performed to identify variants of the DNAH11 gene in the twins. Sanger sequencing and real-time quantitative polymerase chain reaction (RT-qPCR) were used for validation of DNAH11 variants both in the patient and the twins. Results: In the twins, we found a novel mutation at c.2436C > G (p.Y812 *) and a pathogenic deletion encompassing 2.0 Kb of 7P15.3 ([GRCh38] chr7: g.21,816,397-21,818,402). The deleted region included exons 64 and 65 of DNAH11. Sanger sequencing also revealed that the twins’ father was a carrier of heterozygous C.2436C > G and a heterozygous deletion was detected in the mother. No other clinically relevant genetic variants were identified. Conclusion: We describe a novel DNAH11 gene compound heterozygous mutation in newborn twins with PCD and recommend that PCD diagnosis should be considered in newborns presenting with respiratory distress and/or situs inversus. Early diagnosis and treatment of PCD will help control disease progression and improve the patient’s quality of life.